Low-temperature photoionized plasmas induced in Xe gas using an EUV source driven by nanosecond laser pulses. (15th December 2016) - Bartnik, A.; Skrzeczanowski, W.; Wachulak, P.; Saber, I.; Fiedorowicz, H.; Fok, T.; Węgrzyński, Ł.
Abstract: In this work, a laser-produced plasma source was used to create xenon (Xe) photoionized plasmas. An extreme ultraviolet (EUV) radiation beam was focused onto a gas stream, injected into a vacuum chamber synchronously with the EUV pulse. Energies of photons exceeding 100 eV allowed for inner-shell ionization of Xe atoms. Creation of N -shell vacancies resulted in N -shell fluorescence and was followed by multiple ionization. Time-integrated EUV spectra, corresponding to excited states in Xe II–V ions, were recorded. Several emission lines detected in the 39–65 nm wavelength range were not reported earlier. They were not identified due to lack of a corresponding information in published databases. Except spectral measurements in the EUV range, time resolved ultraviolet and visible spectra, originating from Xe II and III ions, were recorded. For spectral lines, corresponding to radiative transitions in Xe II ions, electron temperature was calculated based on a Boltzmann plot method. Based on this method the temperature was measured for different time delays according to the driving EUV pulses.